Dukungan Agama Bagi Kelompok Lansia di Indonesia - Musdah Mulia (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This paper is aimed to offer a solution on the problem of handling the elderly in Indonesia. Increased life expectancy of Indonesia's population affects growing elderly population. So it could be that the twenty first century is called the era of aged population, because the growth of the elderly in Indonesia will be faster than other countries. Indonesia will experience a boom in the number of senior citizens at the beginning of two decades of the 21st century. The elderly in need of handling the complexity of their problems needs to be tackled. One way out of this issue is through social funds for the elderly in Indonesia as a priority. Particular allocation from the social funds, such as, the Muslims’ charity (zakat) and other fundingsources are managed by BAZNAS. Surely, this priority will show the concern of Indonesia’s government for the elderly peoples.